Intercultural Competence Development in ESP Teaching of FutureManagers - Dančišinová, Lucia (Cross-Cultural Education Studies, 2025)
At present, tertiary education is practice-oriented and has to react not only to the requirements of professional orientation but also to the broader socio-economic changes shaping today’s globalized world. In the business sphere, culture has become an increasingly important factor influencing communication, collaboration, and decision-making. As a result of ongoing internationalization and dynamic market developments, future managers are expected to be interculturally competent to be able to communicate effectively in intercultural situations and lead multicultural teams. Therefore, tertiary education of future managers involves ways of intercultural competence development. Raising cultural awareness in the English for Specific Purposes (ESP) classroom is recognized as one of the ways to develop intercultural competence and thus contribute to the necessary soft skills enhancement. The purpose of the study is to describe the possible teaching method used for the intercultural competence development of future managers. At the Faculty of Management and Business of the University of Prešov, the three-step strategy was used with the students enrolled in the ESP course, to identify and explain the elements of culture and how they can help effective communication in intercultural business setting: creation of the identity wheel (one´s cultural elements), application of cultural metaphors (conceptualisation of one´s culture) and comparison of cultural values (cross-cultural comparison). The dominant cultural metaphors and values were selected by a systematic and critical literature review of academic literature. The implications of the study are relevant for the context of intercultural competence development as well as the ESP teaching process.